Transcriptomic and physiological effects of superabsorbent polymer seed coating on maize under drought stress - Abdolmaleki, Akram; Bertram, Hendrik; Dapprich, Peter; Meininghaus, Elena; Michanski, Susann; Schmitz, Michaela; Schmitt, Armin O.; Gültas, Mehmet (Frontiers in Plant Science, 2026)
Drought stress severely impairs maize germination and early seedling growth, posing a significant threat to global food security. To address this, superabsorbent polymers (SAPs) are being explored as an effective seed-coating method to improve water availability during the crucial germination phase. However, their comparative efficacy and underlying molecular mechanisms remain insufficiently understood. In this study, we evaluated the effects of three distinct SAPs, two fossil-based (MERCK, SWT) and one natural-based (ABG), on maize germination and seedling development under controlled drought conditions. We integrated physiological (germination rate and NA+), biochemical (total phenol content), and transcriptomic (mRNA-seq) analyses to provide a comprehensive multi-level assessment. Physiologically, among all SAPs, the MERCK was the most effective, resulting in the highest proportion of normal seedlings and the fewest abnormal seedlings. In contrast, the SWT treatment was detrimental, increasing the proportion of abnormal seedlings, suggesting phytotoxic effects. Biochemically, all SAP treatments resulted in elevated seedling sodium (Na+) content, indicating potential secondary ionic stress. Transcriptomic analysis further elucidated these observations, revealing a set of differentially expressed genes, including those involved in stress response (BADH, FACT, XCP2), SAP-specific response (DRB5, RAF35, EDR1), and combined salt/drought stress (WRKY47, DTX20), as promising candidate biomarkers for stress assessment and breeding. Our research highlights the nuanced efficacy of SAPs; specifically, the MERCK SAP yielded more favorable outcomes, while other formulations occasionally caused unexpected phytotoxicity. The identified gene expression patterns not only mechanistically explain the observed physiological responses but also offer a valuable panel of molecular biomarkers. These markers can be used to screen novel SAP applications, such as seed coatings, and to breed stress-resilient maize cultivars.